2015
DOI: 10.1051/0004-6361/201527254
|View full text |Cite
|
Sign up to set email alerts
|

Detection of extragalactic argonium, ArH+, toward PKS 1830−211

Abstract: Context. Argonium has recently been detected as a ubiquitous molecule in our Galaxy. Model calculations indicate that its abundance peaks at molecular fractions in the range of 10 −4 to 10 −3 and that the observed column densities require high values of the cosmic ray ionization rate. Therefore, this molecular cation may serve as an excellent tracer of the very diffuse interstellar medium (ISM), as well as an indicator of the cosmic ray ionization rate. Aims. We attempted to detect ArH + in extragalactic sourc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 39 publications
2
61
0
Order By: Relevance
“…The (relatively) low number of gas-phase species so far detected in disks can likely be attributed to a combination of factors. Churchwell et al (1977) [4] Fuente et al (2006) [5] García-Burillo et al (2002) [6] Gardner & Whiteoak (1974) [7] Geballe et al (2006) [8] González-Alfonso et al (2004) [9] González-Alfonso et al (2013) [10] Heikkilä et al (1999) [11] Henkel & Bally (1985) [12] Henkel et al (1987) [13] Henkel et al (1988) [14] Johansson (1991) [15] Magain & Gillet (1987) [16] Martin & Ho (1979) [17] Martín et al (2003) [18] Martín et al (2006) [19] Matsuura et al (2002) [20] Mauersberger et al (1990) [21] [22] Mauersberger et al (1995) [23] [24] Monje et al (2011) [25] Muller et al (2011) [26] Muller et al (2013) [27] Muller et al (2014a) [28] Muller et al (2014b) [29] Müller et al (2015) [30] Muller et al (2016) [31] Muller et al (2017) [32] Nguyen-Q- Rieu et al (1991) [33] Petuchowski & Bennett (1992) [34] Qiu et al (2018) [35] Rangwala et al (2011) [36] Rickard et al (1975) [37] Rickard et al (1977) [38] Sage & Ziurys (1995) [39] Seaquist & Bell (1986) [40] Sewiło et al (2018) [41] Stark & Wolff (1979) [42] Thompson et al (...…”
Section: Species Detected In Protoplanetary Disksmentioning
confidence: 99%
“…The (relatively) low number of gas-phase species so far detected in disks can likely be attributed to a combination of factors. Churchwell et al (1977) [4] Fuente et al (2006) [5] García-Burillo et al (2002) [6] Gardner & Whiteoak (1974) [7] Geballe et al (2006) [8] González-Alfonso et al (2004) [9] González-Alfonso et al (2013) [10] Heikkilä et al (1999) [11] Henkel & Bally (1985) [12] Henkel et al (1987) [13] Henkel et al (1988) [14] Johansson (1991) [15] Magain & Gillet (1987) [16] Martin & Ho (1979) [17] Martín et al (2003) [18] Martín et al (2006) [19] Matsuura et al (2002) [20] Mauersberger et al (1990) [21] [22] Mauersberger et al (1995) [23] [24] Monje et al (2011) [25] Muller et al (2011) [26] Muller et al (2013) [27] Muller et al (2014a) [28] Muller et al (2014b) [29] Müller et al (2015) [30] Muller et al (2016) [31] Muller et al (2017) [32] Nguyen-Q- Rieu et al (1991) [33] Petuchowski & Bennett (1992) [34] Qiu et al (2018) [35] Rangwala et al (2011) [36] Rickard et al (1975) [37] Rickard et al (1977) [38] Sage & Ziurys (1995) [39] Seaquist & Bell (1986) [40] Sewiło et al (2018) [41] Stark & Wolff (1979) [42] Thompson et al (...…”
Section: Species Detected In Protoplanetary Disksmentioning
confidence: 99%
“…Molecules tracing gas with a low fraction of molecular hydrogen ( f H 2 ) preferentially, such as ArH + , OH + , H 2 O + , and H 2 Cl + , are found to have enhanced abundances along the NE line of sight relative to the SW one (Muller et al 2014a;Müller et al 2015;Muller et al 2016a). Among other evidence, this observation suggests that the absorbing gas in the NE line of sight is more diffuse.…”
Section: Description Of the Sourcementioning
confidence: 99%
“…Moreover, features of 38 ArH + were subsequently found in Sg B2(M) as well and, consequently, Schilke et al suggested that argonium is ubiquitous in the ISM. More recently, Müller et al (2015) made extragalactic detections of the 36 Ar and 38 Ar isotopologues of argonium through absorption studies of a foreground galaxy E-mail: vincenzo.laporta@univ-lehavre.fr (VL) at z = 0.89 along two different lines of sight toward PKS 1830-211 within the band 7 of the ALMA interferometer, including the corresponding redshifted transitions.…”
Section: Introductionmentioning
confidence: 99%